Solutions to develop human resources for marine resources and environment management in the new context - Thai Quang The; Nguyen Thi Ly (Journal of State Management, 2024)
To realize the goals of making Vietnam a strong marine nation, prosperous from the sea, ensuring the marine environment, and firmly protecting national sovereignty over its seas and islands, the human resources for marine resources and environment management need to be improved. In the current context, human resources of this sector have exposed several limitations, failing to effectively meet the requirements of state management of seas and islands. Therefore, if this situation is not promptly remedied, the national strategic goal of economic development linked with environmental protection and the defence of maritime sovereignty will be hard to achieve. This article contributes to an overview of research related to the development of human resources for marine resources and environment management, pointing out the achievements as well as the existing problems, analysing, evaluating, and proposing a number of solutions to improve the quality of Vietnam’s human resources for marine resources and environment management in the coming time.